2009
DOI: 10.15288/jsad.2009.70.78
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Cognitive Influences on Drinking and Alcohol Problems

Abstract: ABSTRACT. Objective:We explored the relationships between two domains of alcohol-related cognitions (expectations and reasons for drinking) and their associations with alcohol consumption and alcohol dependence. It is hypothesized that alcohol-related cognitions will relate directly to drinking behaviors and indirectly to alcohol dependence. Method: Data came from the 1995 National Alcohol Survey, which included black and Hispanic oversamples. The analysis was restricted to 2,817 respondents who reported alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…Alcohol expectancies , or the beliefs about the effects/consequences of alcohol, are also predictive of alcohol consumption and problems (Fromme & D'Amico, 2000; Greenfield, Harford, & Tam, 2009; Pabst, Kraus, Piontek, Mueller, & Demmel, 2014). Approaches that challenge and modify these expectancies have been shown to reduce alcohol use in the short-term (Lau-Barraco & Dunn, 2008; NIAAA, 2002; Scott-Sheldon, Terry, Carey, Garey, & Carey, 2012).…”
mentioning
confidence: 99%
“…Alcohol expectancies , or the beliefs about the effects/consequences of alcohol, are also predictive of alcohol consumption and problems (Fromme & D'Amico, 2000; Greenfield, Harford, & Tam, 2009; Pabst, Kraus, Piontek, Mueller, & Demmel, 2014). Approaches that challenge and modify these expectancies have been shown to reduce alcohol use in the short-term (Lau-Barraco & Dunn, 2008; NIAAA, 2002; Scott-Sheldon, Terry, Carey, Garey, & Carey, 2012).…”
mentioning
confidence: 99%
“…As the TPB notes, the expected consequences of a behavior are an important factor to consider when predicting whether the behavior is more or less likely to occur (Ajzen, 1998, 1991; Conner et al, 2006). Individuals who expect consuming alcohol to produce positive outcomes are more likely to drink, drink more frequently, and drink more heavily than those with more negative alcohol expectancies (Fromme & D’Amico, 2000; Greenfield, Harford & Tam, 2009; Natvig Aas, Leigh, Anderssen & Jakobsen, 1998). Future research may include alcohol expectancies to examine whether they impact the moderating effect of SC on the relationship between SRDI and drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Greenfield, Harford and Tam (2009) suggested that differences in culture might be crucial in the development of alcohol expectancies and the associated drinking patterns. Oei and Jardim (2007) compared the alcohol related behaviours of Asian and Caucasian students in Australia, a drinking culture similar to England.…”
Section: Outgoing and Friendly' 'If I'm Drinking It's Easier To Exprmentioning
confidence: 99%
“…Findings of the US National Alcohol Survey (1995), also found that individuals of white origin drank more heavily than those of black origin. When those of black ethnicity reported that they drank heavily, they were then more at risk of becoming alcohol dependent (Greenfield, Harford &Tam, 2009). High positive alcohol expectancies such as assertion, Drinking outcome expectancies and normative perceptions of students engaged in university sport 16…”
Section: Outgoing and Friendly' 'If I'm Drinking It's Easier To Exprmentioning
confidence: 99%